1997
DOI: 10.1524/ract.1997.79.1.63
|View full text |Cite
|
Sign up to set email alerts
|

Direct Labeling of Monoclonal Antibodies and Antibody Fragments with 188Re Using a Weak Competing Ligand

Abstract: Different kit formulations for the direct labeling of MoAb-IOR CEAl and its F(ab')2 fragments with Rhenium-188, using EHDP as a weak competing ligand, were developed. The influence of reaction conditions such as pH, temperature, weak ligand concentration and stannous Chloride concentration during the preparation of '""Re-MoAb radioimmunoconjugates, were investigated in detail in order to obtain high radiochemical yields. Results showed that under different reaction conditions, radiochemical purities Over 95% w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…Increased effort has been made to label mAbs with rhenium-188, samarium-153, yttrium-90, and lutetium-177 because of their potential role in the radioimmunotherapy of cancer ( ). However, the radiolabeling of mAbs or F(ab') 2 fragments with Sm-153 by combination of avidin−biotin strategy has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Increased effort has been made to label mAbs with rhenium-188, samarium-153, yttrium-90, and lutetium-177 because of their potential role in the radioimmunotherapy of cancer ( ). However, the radiolabeling of mAbs or F(ab') 2 fragments with Sm-153 by combination of avidin−biotin strategy has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Recently it has been shown that 90 Y labelled Mab fragments are effective at curing small tumors with relatively few side effects [162]. On the other hand, increased effort has been made to label Mabs with rhenium-188, because of its potential role in the RIT of cancer and the recent availability of 188 Re from a W-188/Re-188 generator [163,164].…”
Section: Monoclonal Antibodies and Their Fragmentsmentioning
confidence: 99%
“…Oliver e colaboradores usaram 1,67 mg de SnF 2 (correspondente a 1,26 mg de Sn 2+ ) e obtiveram um bom rendimento de marcação com uma atividade de 188 Re de 1,5 -1,9 GBq (40,5 -51,3 mCi) (Oliver et al, 2005). (Perera et al, 2003;Ferro-Flores & Hashimoto, 1997;Kodina et al, 2005). O efeito da massa de tartarato foi estudado e os resultados encontrados estão demonstrados na FIG.…”
Section: Marcação Direta: Variáveis E Análise Radioquímica Usando Cp unclassified